Formant frequencies of normal Malaysian Indian young adults in sustained vowels - Ting, H.N.; Lee, C.H. (2012)
This paper investigates the first four formant frequencies of 60 normal Malaysian Indian young adults in sustained vowels using acoustical analysis. The F1, F2, F3 and F4 of Malaysian Indian males were reported at 359±87 Hz, 1457±630 Hz, 2799 ±336 Hz and 3777 ± 299 Hz respectively. The F1, F2, F3 and F4 of Malaysian Indian females were reported at 485±172 Hz, 1707±746 Hz, 3081±330 Hz and 4305±288 Hz respectively. Malaysian Indian females had significant higher formant frequencies in all vowels than those of Indian males except F2 and F3 in /u/. Besides that, significant differences in all the formant frequencies were observed across all the vowels for both Indian males and females. Significant interactions between vowels and gender were found in F1, F2 and F3 but not in F4.